PHENOL ADSORPTION USING COMPOSITE ADSORBENT Fe3O4-ACTIVATED CHARCOAL COFFEE GROUNDS - Elen Reknosari; Teguh Wirawan; Soerja Koesnarpadi (JURNAL KIMIA MULAWARMAN, 2020)
ABSTRACT Phenol adsorption using composite adsorbent Fe3O4-activated charcoal coffee grounds has been done. Composite adsorbent Fe3O4 -activated charcoal coffee grounds are synthesized from FeSO4. 7H2O and FeCl3. 6H2O with a ratio of 3: 2 and then compiled with activated coffee charcoal. The composite adsorbent Fe3O4-activated coffee charcoal was characterized by Fourier Transform Infared (FTIR) and Scanning Electron Microscopy (SEM) as well as the adsorption test on phenol. The results of the characterization with Fourier Transform Infared (FTIR), peak 1604.77 cm-1 appeared showing the absorption of C=O which states that coffee grounds have formed carbon. Beside that, Fe3O4-activated charcoal composite adsorbent peaks appear at a wavelength of 509.21 cm-1 which is a Fe-O group showing that Fe3O4 nanoparticles have been successfully grafted on the active charcoal structure. The optimum conditions of phenol adsorption using adsorbent composite Fe3O4-activated coffee grounds at 30 minutes contact time and pH 5. Keywords: Adsorption, Phenol, Magnetite, Active Charcoal, Coffee Grounds